Estudos dos mecanismos que influenciam o padrão de escoamento e transporte de massa do escalar passivo em diferentes configurações de matriz - Corrêa, Nathalia Ribeiro (2021)
The mechanisms that influence the flow pattern and mass transport of the passive scalar in an urban environment were studied. The understanding of the dispersion of pollutants is not something simple to be studied due to the complexity that the obstacles generate in the atmospheric flow. Thus, there are gaps that must be investigated to better understand the processes that act in the transport of the pollutant, being a subsidy, for example, in the aid for decision making in emergency situations. In this study, the behavior of the flow and the dispersion of a scalar in different array configurations were evaluated. Firstly, the behavior of the plume and the flow dispersion and concentrations inside and above the canopy were evaluated, by means of horizontal and vertical fluxes that act in the transport of the scalar in the array, in an array of cubic buildings, aligned and of the same height. It was noted that the canyon regions capture pollutants due to recirculation. As for scalar fluxes, it was noticed that the vertical flux increases its participation in the transport of the pollutant out of the canopy as it moves away from the source of the source, especially at intersections. However, it was concluded that the horizontal flux is dominant in the transport of the scalar inside the canopy. The street network model and reference data from LES and DNS simulations and from wind tunnel experiments in idealized array, composed of buildings of the same height and rectangular, were used. The objective was to promote an asymmetric effect in the array, in contrast to idealized models in which the arrays are composed of square buildings. The array of rectangular buildings increases the complexity of the flow in the canopy analysis to create long streets, moving closer to reality, especially in European cities. That said, the influence of wind direction, source location and geometry of buildings in the array on the dispersion of a scalar in the urban canopy was evaluated. The application of the street model was corroborated for studies of urban dispersion in idealized arrays, showing that the model can predict the behavior of the plume and profiles of average concentrations, capturing the effects of topological dispersion. The wind direction, associated with the location of the source showed that the channeling of the flow is favored when the flow approaches parallel to the location of the source, resulting in average concentrations that are higher in the flow direction. In addition, regarding the influence of the geometry of the array, it was clear that the greater length of the streets favors the vertical transport of climbing out of the canopy. Thus, concentrations decline more quickly within the urban canopy when the array is made up of square buildings.